ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI, DAN SUKU BUNGA TERHADAP KREDIT MACET DI INDONESIA - Abd. Rizal; T. Zulham; Asmawati Asmawati (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
Abstract This study aimed to analyze the effect of Macroeconomic variables in the form of Economic Growth, Inflation and interest rate of Bank Indonesia (7-Day Repo rate) on Non Performing Loans (NPL) in Indonesia. This study uses annual time series data from 2000 to 2017 with a total sample of 18 years. The model used is Auto Regressive Distributed Lags (ARDL) using Eviews 9. Software The results show that in the short run Inflation has a negative effect on Non Performing Loans (NPL) and Inflation in the previous year  (Lag-1) has a significant positive effect whereas in the long run Inflation has a negative effect, maintained inflation at a reasonable limit to foster a good climate for entrepreneurs to be a stimulus so that they are able to fulfill their obligations, in the long run Economic growth has a significant negative effect and interest rates have a significant positive effect. It is hoped that the government can be more careful in setting the 7-Day Repo rate, given the positive response shown to Non Performing Loans (NPL). In addition, the government must also be able to maintain sustainable economic growth given its negative relationship to Non Performing Loans (NPL). It is recommended for further researchers to add other variables such as stock index, exchange rate, Capital Adequacy Ratio (CAR) and Charge-off policy (PH) of non-performing loans.